Scintigraphic Phase Analysis of Abnormal A-V Conduction in a Baboon - Dormehl, Irene C.; Hugo, N.; Van Gelder, A.; Maree, M.; De Winter, R.; Jacobs, L. (Nuklearmedizin - NuclearMedicine, 1988)
During an interventional cardiac investigation on an anaesthetised baboon (Papio ursinus) the animal developed A-V block. Scintigraphic phase analysis leading to quantified intraventricular delays and histogram characteristics pointed to abnormalities which persisted even after A-V block was replaced by nodal tachycardia as was reflected by the electrocardiogram. This indicated towards an increased diagnostic sensitivity with the use of phase analytical methods.Während einer eingreifenden Herzuntersuchung an einem narkotisierten Pavian (Papio ursinus) entwickelte das Tier einen A-V-Block. Die szintigraphische Phasenanalyse deutete auf vermehrte intraventrikuläre Verzögerungen und abnormale Histogram-Charakteristika hin, die sogar nach Übergang des A-V-Blocks in eine nodale Tachykardie anhielten. Dies wies auf eine erhöhte diagnostische Sensitivität der phasenanalytischen Methoden hin.